Finite element modelling of stress distribution in spherical liquified natural gas (LNG) pressure vessels (2011)
"This work investigated the distribution of Von Misses stress in LNG Spherical Carbon Steel Storage tanks. Using the Finite Element Method and equations of elasticity, constant thickness carbon steel spherical storage tanks of 40 in. dia. 70in. dia of 1 in. shell thickness were subjected to different loading conditions from 500 to 4000Psi in incremental of 500 Psi. Spherical triangular elements based on shallow shell formulation were used for the model. The element has five degrees of freedom at each corner node, which are the essential external degrees of freedom without the degree of freedom associated with the in-plane shell rotation. The displacement fields of the element satisfy the exact requirement of rigid body modes of motion. The FORTRAN 90 coding was developed to obtain maximum Von Misses stress distribution with the tank subjected to different internal pressure and wind loadings. The results were then compared with the yield stress of the material of the tank. Von Misses stress is used as yield criteria whether to change tank material or increase the shell material thickness if yield stress is higher than the Von-Misses Stress. Results showed Von Mises stresses for a 40 in dia. Spherical shell with 1 in shell thickness able to withstand internal pressure loading alone up to 3500 Psi after which the shell thickness will no longer be able to withstand the loading. The 70in. dia. Vessel could only withstand internal pressure loading up to 2000 Psi. Validation of Finite Element modeling was done using ASME Section VIII Div 1 standard. Modeled results were observed not to be significantly different from ASME values (P>0.05). External wind effects alone on small dia. vessels was seen to be constant for all sides of the pressure vessel.